Transformations : Harriet and Helena Scott, colonial Sydney's finest natural history painters - Finney, Vanessa; McKay, Kim; Ogders, Sarah; Australian Museum. Trust (Sydney, NSW : NewSouth Publishing, 2018)
"Harriet and Helena Scott transformed nature into art in their extraordinary paintings of butterflies and moths. With their collecting boxes, notebooks and paintbrushes, Harriet and Helena entered the masculine worlds of science and art and became two of nineteenth-century Australia's most prominent natural history painters. Transformations reveals the talented Scott sisters' captivating story for the first time - their early lives spent in colonial Sydney, their training as naturalists and artists by their father AW Scott, the productive years living and working on isolated Ash Island near Newcastle from 1846, and their professional challenges and triumphs."--Dust jacket gate fold.
Illustrations on end papers.
Includes bibliographical references (pages 205-211) and index.
Keywords: Scott, A. W. (Alexander Walker), 1800-1883 -- Family; Forde, Helena, -- 1832-1910.; Scott, Harriet, -- 1830-1907.; Natural history illustrators -- Australia -- Biography; Naturalists -- Australia -- Biography; Zoological illustration -- Australia -- History; Painting, Australian -- 19th century -- Pictorial works; Lepidoptera -- Australia -- Pictorial works; Butterflies in art; Moths in art; Ash Island (N.S.W.) -- Environmental conditions -- History; Ash Island (N.S.W.) -- History; Australian